Development and validation of a HPLC analytical assay method for efavirenz tablets: a medicine for HIV infections - Osnir de Sá Viana; Flávia Patrícia Morais Medeiros; Severino Grangeiro-Júnior; Miracy Muniz Albuquerque; Mônica Felts La Roca Soares; José Lamartine Soares-Sobrinho; Lariza Darlene Santos Alves; Larissa Araújo Rolim; Keyla Emanuelle Ramos da Silva; Pedro José Rolim-Neto (Universidade de São Paulo, 2011)
Efavirenz is a reverse transcriptase non analog nucleoside inhibitor used to treat HIV infections. A simple assay method by high performance liquid chromatography was developed and validated for efavirenz tablets. The physical chemical characteristics of efavirenz were investigated to developing the method. The method was validated observing the parameters described in USP 29. Analyses were performed by an ultraviolet detector at a 252 nm wavelength, on a reverse-phase column (C18, 250 mm x 3.9 mm, 10 μm), using an isocratic mobile phase containing acetonitrile/water/orthophosphoric acid (70:30:0.1). The validation parameters used were: selectivity, linearity, precision, accuracy, robustness, detection and quantification limits, and all resulting data were treated by a statistical method. The results obtained confirmed an alternative assay method for efavirenz tablets adequate for routine industrial use. O efavirenz é um inibidor não análogo de nucleosídeo da transcriptase reversa, utilizado no tratamento da infecção por HIV. Um método simples, por cromatografia líquida de alta eficiência, foi desenvolvido e validado para quantificação do efavirenz em comprimidos. O desenvolvimento do método levou em consideração as características físico-químicas do efavirenz. O método foi validado seguindo os parâmetros da USP 29. A análise foi realizada por meio de detector ultravioleta, utilizando um comprimento de onda de 252 nm, com coluna de fase reversa (C18, 250 mm x 3.9 mm, 10 μm) e fase móvel isocrática contendo acetonitrila/água/ácido ortofosfórico (70: 30: 0.1). Os critérios usados para validação foram: seletividade, linearidade, precisão, exatidão, robustez e limites de detecção e quantificação do método. Foi utilizado método estatístico em todas as etapas do processo de validação. Os resultados obtidos mostraram que o método é uma alternativa para quantificação do efavirenz em comprimidos, tornando viável seu uso na rotina industrial e laboratórios analíticos.